ORA47 is a transcriptional regulator of a general stress response hub. (24th February 2022) - Zeng, Liping; Chen, Hao; Wang, Yaqi; Hicks, Derrick; Ke, Haiyan; Pruneda‐Paz, Jose; Dehesh, Katayoon
SUMMARY: Transcriptional regulators of the general stress response (GSR) reprogram the expression of selected genes to transduce informational signals into cellular events, ultimately manifested in a plant's ability to cope with environmental challenges. Identification of the core GSR regulatory proteins will uncover the principal modules and their mode of action in the establishment of adaptive responses. To define the GSR regulatory components, we employed a yeast‐one‐hybrid assay to identify the protein(s) binding to the previously established functional GSR motif, termed the rapid stress response element (RSRE). This led to the isolation of octadecanoid‐responsive AP2/ERF‐domain transcription factor 47 (ORA47), a methyl jasmonate inducible protein. Subsequently, ORA47 transcriptional activity was confirmed using the RSRE‐driven luciferase (LUC) activity assay performed in the ORA47 loss‐ and gain‐of‐function lines introgressed into the 4xRSRE::Luc background. In addition, the prime contribution of CALMODULIN‐BINDING TRANSCRIPTIONAL ACTIVATOR3 (CAMTA3) protein in the induction of RSRE was reaffirmed by genetic studies. Moreover, exogenous application of methyl jasmonate led to enhanced levels of ORA47 and CAMTA3 transcripts, as well as the induction of RSRE::LUC activity. Metabolic analyses illustrated the reciprocal functional inputs of ORA47 and CAMTA3 in increasing JA levels. Lastly, transient assays identified JASMONATE ZIM‐domain1 (JAZ1) as a repressor of RSRE::LUC activity. Collectively, the present study provides fresh insight into the initial features of the mechanism that transduces informational signals into adaptive responses. This mechanism involves the functional interplay between the JA biosynthesis/signaling cascade and the transcriptional reprogramming that potentiates GSR. Furthermore, these findings offer a window into the role of intraorganellar communication in the establishment of adaptive responses. Significance Statement: The present study unmasks the initial mechanistic features of adaptive responses that include tight cooperativity between the jasmonate biosynthesis and signaling cascade and the nuclear transcriptional machinery comprising two activators (CAMTA3 and ORA47) and a suppressor JAZ1. The work further identifies CAMTA3 as a functional link between jasmonate signaling and activation of a general stress transcriptional hub.